Zarządzanie procesowe w organizacjach publicznych - Zioło, Magdalena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The article presents the role of Business Process Reengineering (BPR) in the enhancement of public sector effectiveness. This paper seeks to present a review of reengineering fundamentals and an analysis of the practice of the technique, which could be implemented in various public organizations. To provide a framework for the use of reengineering among public sector organizations, a brief overview will also be presented on the philosophies, stages and strategies that have evolved in recent years and created common concept of BPR. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 52-59